ملكية المعادن في الفقه الإسلامي - عبد الستار, كمرشو (University of Eloued جامعة الوادي, 2017)
هذه الدراسة الموسومة: ملكية المعادن في الفقه الإسلامي، وتكمن أهميتها أنها تكتسي الأهمية البالغة في حياة الإنسان لا يمكنه الاستغناء عنه ,وكان الإشكال الرئيس الذي تسعى للإجابة عليه هو :ما مدى اتفاق اجتهادات الفقهاء المسلمين في ملكية المعادن؟ أجابت الدراسة على ذلك من خلال أربعة مباحث وهي :المبحث الأول خصصته لمفهوم الملكية: تعريفها, أسبابها, أنواعها. أما المبحث الثاني فقد جعلته لمفهوم المعادن :تعريفها أنواعها أما المبحث الثالث اتجاهات الفقهاء في ملكية المعادن: القائلون بالملكية الخاصة للمعادن والقائلون بالملكية العامة للمعادن والقائلون بمبدأ الإباحة بملكية المعادن، أما المبحث الأخير المعادن ومدى استثمارها في الاقتصاد الإسلامي: الحقوق المالية المتوجبة عن المعادن وطابعها الاستثماري ،أسس النمط الاستثماري في ظل مبدأ ملكية الدولة للمعادن ومبدأ الإباحة.This study tagged: Ownership of minerals in the Islamic Jurisprudence .Their importance liesIt is of critical importance In human life Can not do without, It was the main problemWhich seeks To answer it is:To what extent do the jurisprudence of Islamic jurists agree In the ownership of minerals?She replied studyOn it through three sections are:The first section allocated to the concept of ownership:Definition, causes, types.The second sectionIt has made him the concept of metals:Definition, types. The third section Trends of fuqaha in the ownership of minerals: Sayers Private property of metals ,And Sayers Public property of metals. The last section Minerals and the extent of their investment in the Islamic economy: The financial rights of minerals and their investment nature , He founded the investment pattern in the light of the principle of state for metals.
مذكرة ماستر تخصص معاملات مالية
Keywords: الملكية - المعادن – المعاملات المالية - الفقه الإسلامي; Property - Metals - Financial Transactions - Islamic Jurisprudence